2021
DOI: 10.1155/2021/3006853
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Therapeutic Mechanisms of Curcumin in Osteosarcoma: State-of-the-Art

Abstract: Osteosarcoma is a major form of malignant bone tumor that typically occurs in young adults and children. The combination of aggressive surgical strategies and chemotherapy has led to improvements in survival time, although individuals with recurrent or metastatic conditions still have an extremely poor prognosis. This disappointing situation strongly indicates that testing novel, targeted therapeutic agents is imperative to prevent the progression of osteosarcoma and enhance patient survival time. Curcumin, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 111 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…Cao et al [110] experimentally found that cinobufotalin was able to inhibit Notch signaling pathway, decrease the expression of Notch-1, Hes-1, Hes-5 and Hey-1 genes in OS cell lines, inhibit OS cell survival and induce OS cell apoptosis, and then inhibit the growth of transplanted tumors in mice. Similarly, Farnood et al, Zahedipour et al [92,111] applied curcumin to OS cells, and found that this compound could also downregulate Notch-1, Hes-1, Hey-1, and Hey-2 mRNA expression levels, inhibit cyclin D1, MMP-2, and MMP-9 protein expression levels, and regulate tumor cell growth, inflammatory expression, and apoptotic progression by inhibiting the Notch signaling pathway, so as to have the properties of anti-inflammatory, anti-oxidant, and anti-cancer. Niu et al [112] experimentally found that cannabinoids down-regulated the expression of Notch-1, MMP-2 and VEGF through the Win/Notch signaling pathway, which could not only inhibit the generation of tumor collateral vessels, but also inhibit the proliferation, metastasis and invasion of OS cells.…”
Section: Targeted Therapy Of Os By Signaling Cascade Associated With ...mentioning
confidence: 94%
See 1 more Smart Citation
“…Cao et al [110] experimentally found that cinobufotalin was able to inhibit Notch signaling pathway, decrease the expression of Notch-1, Hes-1, Hes-5 and Hey-1 genes in OS cell lines, inhibit OS cell survival and induce OS cell apoptosis, and then inhibit the growth of transplanted tumors in mice. Similarly, Farnood et al, Zahedipour et al [92,111] applied curcumin to OS cells, and found that this compound could also downregulate Notch-1, Hes-1, Hey-1, and Hey-2 mRNA expression levels, inhibit cyclin D1, MMP-2, and MMP-9 protein expression levels, and regulate tumor cell growth, inflammatory expression, and apoptotic progression by inhibiting the Notch signaling pathway, so as to have the properties of anti-inflammatory, anti-oxidant, and anti-cancer. Niu et al [112] experimentally found that cannabinoids down-regulated the expression of Notch-1, MMP-2 and VEGF through the Win/Notch signaling pathway, which could not only inhibit the generation of tumor collateral vessels, but also inhibit the proliferation, metastasis and invasion of OS cells.…”
Section: Targeted Therapy Of Os By Signaling Cascade Associated With ...mentioning
confidence: 94%
“…Hederoside C P. koreana MG-63, U2OS [100] Salidroside Rhodiola rosea L. U2OS, MG-63 [101] Tubocapsenolide A Tubocapsicum anomalum SHP-2 [102] Andrographolide Andrographis paniculata U2OS [103] Pacilitaxel Taxus wallichiana var. chinensis (Pilger) Florin U2OS, MG-63 [104] Resveratrol Veratrum album MNNG/HOS, MG-63 [105] β-caryophyllene Dianthus chinensis L. MG-63 [106] Sodium cantharidate Mylabris phalerata Pallas MG-63 [107] Tanshinone I Salvia miltiorrhiza Bunge U2OS, MOS-J [108,109] Notch pathway Cinobufagin Bufo raddei U2OS, MG-63 [110] Curcumin Curcuma longa L. U2OS [92,111] Cannabinoids Cannabis sativa L. MG-63 [112] Dihydroartemisinin Artemisia caruifolia Buch.-Ham. ex Roxb.…”
Section: Mg-63mentioning
confidence: 99%
“…For instance, the synthesis of vancomycin derivative T-methyl chloride can stabilize HIF-1α protein and activate its transcriptional activity, thereby inducing gene expression of downstream targets such as VEGF and GLUT-1 ( Magae et al, 2019 ). Moreover, curcumin exerts multiple inhibitory effects on OS metastatic cells including cell adhesion and vascular remodeling ( Zahedipour et al, 2021 ). Therefore, anti-angiogenesis may simultaneously target multiple molecular mechanisms involved in the process of OS metastasis, making it the most promising therapeutic approach for inhibiting OS metastasis.…”
Section: Therapeutic Prospect Of Targeting Hif-1α In the Treatment Of...mentioning
confidence: 99%
“…Yu et al (2021) demonstrated the development of Cur-loaded chitosan nanoparticles encapsulated in a methacrylated silk fibroin/hyaluronic acid (CCNPs-SF/HAMA) hydrogel, which proved to be effective in reducing the viability of osteosarcoma cells and promoting the proliferation of osteoblasts in vitro [ 94 ]. Cur, a natural polyphenol derived from turmeric Curcuma longa, has shown anti-tumor, anti-oxidant, and anti-inflammatory activities against osteosarcoma, as well as increased osteoblast proliferation and bone formation [ 95 , 96 , 97 ]. The CCNPs-SF/HAMA hydrogels loaded with Cur demonstrated that 150 μg/mL of Cur demonstrated simultaneous anti-cancer effects in MG-63 cell cultures, significantly decreasing cell viability from 100% to approximately 56% and osteoblast proliferative effects in MC3T3-E1 cell cultures, significantly increasing the cell viability from 100% to 124.5% ( Figure 4 ) [ 98 ].…”
Section: Hydrogels For Osteosarcoma Therapymentioning
confidence: 99%